Penyebab Rendahnya Kemampuan Literasi Anak Kelas III Di SD Negeri 0117 Sibuhuan - Irma Sari Daulay; Rizky Hamdan Saputra; Irma Juita (Simpati, 2023)
The aim of this research is to find out: (1) The literacy skills of class III children at SD Negeri 0117 Sibuhuan. (2) Internal and external factors cause the low literacy skills of class III students, especially in reading and writing at SD Negeri 0117 Sibuhuan. Based on the results of the research and discussion in this study, it can be concluded that: (1) The habituation of literacy skills in class III of SD Negeri 0117 Sibuhuan is reading books every day before learning and the teacher also guides students to read books related to the school literacy movement so that students do not feel stressed and bored in reading. Apart from that, teachers also encourage students to participate in making posters, information boards (mading), and literacy trees. It is hoped that this will help foster the school literacy movement, which in turn can shape students' character for the future. (2) Internal and external factors causing the low literacy skills of class III students, especially in reading and writing at SD Negeri 0117 Sibuhuan, namely: (a) In the aspect of students, including students, there are problems in articulating the pronunciation of words, often pronouncing words -words that are not clear enough, and still often mispronounce words in one sentence. Apart from that, students face difficulties in understanding the meaning contained in the reading. (b) The lack of reading habits among students is caused by a lack of awareness of the importance of reading books. Students prefer to spend their time on other activities rather than reading, both in class and in the librar